The Effect of Operation and Engine Speed on Chainsaw Vibration - M Feyzi (Ferdowsi University of Mashhad, 2018)
Introduction Tree felling is an important part of forest exploitation. According to the condition of Iranian forests, mechanization in these forests has not been grown as it should be. Therefore, a main part of tree felling operations are performed by chainsaw. This machine can cause high level hand-arm vibration which is one of the main reasons of white finger syndrome. This syndrome affects the nerves, blood vessels, muscles, and joints of the hand, wrist, and arm. Reducing and controlling chainsaw vibrations are unlikely to be achievable without awareness of effective factors of it. So, the effects of various factors should be studied. It seems that, single cylinder engine and the interaction of the chain with wood can be the main reasons of chainsaw vibration. Therefore, in the current study the effects of engine rotary speed and wood type on the vibration acceleration of a common chainsaw have been investigated. In contrast to the previous studies, no-cutting condition as a control sample was added to experiments and the effects of cutting itself were evaluated. Experiments were also conducted in three different engine speeds to investigate the effects of interaction between wood species and engine speed. Materials and Methods The vibration acceleration was measured on three orthogonal axes on the front handle of Stihl-070 chainsaw. The measurements were conducted at three levels of engine speed (6000, 7720, and 8630 RPM) during four operations. The operations include cutting three types of Iranian woods (Beech, Hornbeam, and Alder) and no-cutting as a control sample. The experiments were conducted in split-factorial design where the operation was taken as main plot and different speeds and directions as factors. A single-axis piezoelectric accelerometer (VMI-192) was used to sense the vibration. Vibration signals were received and analyzed by a portable data acquisition system (Easy Viber). The RMS vibration acceleration at one-third octave frequency bands in the center frequency range between 6.3Hz to 1250Hz were calculated from acceleration-frequency vibration spectra. Then, the amounts of frequency-weighted vibration acceleration (ahw) were computed based on international standards. SAS software was used to analyze the data statistically. Results and Discussion The results of ANOVA showed that the effect of operation on frequency-weighted acceleration was insignificant, but the effects of engine speed and vibration axis were significant at the 1% level. When the chainsaw was free of cutting, the vibration acceleration values were lower in lower frequencies and higher in higher frequencies compared to cutting wood operations. There was a significant difference between the vibration acceleration in 6000 RPM engine speed and other two speeds, but the differences between 7720 RPM and 8630 RPM engine speeds was insignificant. However, an increase in engine rotary speed increased the value of frequency-weighted vibration acceleration. The acceleration-frequency vibration spectra had peaks at frequencies in accordance with the engine combustion frequencies (100 Hz in 6000, 125 Hz in 7720, and 160 Hz in 8630). Maximum value of unweighted vibration acceleration was observed during no-cutting operations in 6000, 7720, and 8630 RPM engine speeds to be 77.2, 138.6, and 139.0 m s-2, respectively. Vibration acceleration was highest along the Xh (perpendicular to the palm area) equal to 12.05 m.s-2 followed by Yh axis (along the third metacarpal bone) with the value of 9.12 m s-2. Altogether, the results of these tests indicated that the vibration level of employed chainsaw in this study is very higher than other machines has been investigated by other researchers. Conclusions The effects of wood species and engine speed on the hand-transmitted vibration of chainsaw were evaluated. The operation has not significantly affected the frequency-weighted vibration acceleration. However, cutting operations, increase and decrease the vibration acceleration values in lower and higher frequencies, respectively. The frequency-weighted vibration acceleration had higher values in higher engine speeds. Also, it is concluded that the risk of white finger syndrome among the operators of this type of chainsaw is very high.